Levels of immunoglobulin”“A in trachea, gut and bile samples of chickens vaccinated against newcastle disease - Perozo, Francisco; Finol, Giovanny; Mavárez, Yaneth (Revista Científica de la Facultad de Ciencias Veterinarias)
Immunoglobulin-A (IgA) response to Newcastle diseases virus (NDV) vaccination was assessed using enzyme-linked immunosorbent assay. Total and NDV specific IgA levels were determined in tracheal washings, intestinal washings and bile. Chickens were primed with an in ovo recombinant avian adeno-associated vaccine coding for the NDV hemagglutinin-neuraminidase gene (rAAAV) and revaccinated with B1 or La-Sota strains of the virus. The most suitable samples for IgA determinations were tracheal washings and bile. No NDV specific IgA response was elicited by the rAAAV alone. After revaccination with live NDV virus the IgA levels in the biological samples were significantly higher (P menor 0.005) than the levels in the unvaccinated controls. No strain dependant differences were observed in the NDV specific response after revaccination. Nodifferences in total (unspecific) IgA levels between control and vaccinated birds were observed. In view of the importance of mucosal immune response to NDV infection, the assessment of local antibody levels can aid in the study of the host antiviral response.